2016
DOI: 10.1063/1.4942662
|View full text |Cite
|
Sign up to set email alerts
|

Co on Fe3O4(001): Towards precise control of surface properties

Abstract: A novel approach to incorporate cobalt atoms into a magnetite single crystal is demonstrated by a combination of x-ray spectro-microscopy, low-energy electron diffraction, and density-functional theory calculations. Co is deposited at room temperature on the reconstructed magnetite (001) surface filling first the subsurface octahedral vacancies and then occupying adatom sites on the surface. Progressive annealing treatments at temperatures up to 733 K diffuse the Co atoms into deeper crystal positions, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Note that the incorporation of Co causes the Fe int atom to diffuse to a Fe oct site resulting in the lifting of the SCV reconstruction locally (see dashed arrows in Figure 90. Gargallo-Caballero et al [526] observed that deposition of 1 ML Co leads to the lifting of a (1×1) LEED pattern, consistent with this idea. Gargallo-Caballero et al also studied much higher Co coverages (between 1 and 25 ML) using LEED, PEEM, XMCD and XAS and DFT+U calculations, and determined that Co first occupies the subsurface vacancies for coverages up to one Co 2+ atom per unit cell, after which the Co 1 adatom sites are occupied by Co 2+ species.…”
Section: Cobaltsupporting
confidence: 73%
“…Note that the incorporation of Co causes the Fe int atom to diffuse to a Fe oct site resulting in the lifting of the SCV reconstruction locally (see dashed arrows in Figure 90. Gargallo-Caballero et al [526] observed that deposition of 1 ML Co leads to the lifting of a (1×1) LEED pattern, consistent with this idea. Gargallo-Caballero et al also studied much higher Co coverages (between 1 and 25 ML) using LEED, PEEM, XMCD and XAS and DFT+U calculations, and determined that Co first occupies the subsurface vacancies for coverages up to one Co 2+ atom per unit cell, after which the Co 1 adatom sites are occupied by Co 2+ species.…”
Section: Cobaltsupporting
confidence: 73%
“…The XPS and EDX analysis of the Co@Fe 3 O 4 nanozyme demonstrated that the cobalt atoms were probably located only at the lattice positions of the Fe 3 O 4 crystal structure. Although the Co atom possesses a similar size as the Fe atom, the Co atoms doped into the Fe 3 O 4 crystal may still slightly change the surface physical environment, 35 resulting in an improved binding affinity of the nanozyme to H 2 O 2 . In addition, the Co dopant may produce more catalytically active sites and substrate-binding sites on the surface of the Co@Fe 3 O 4 nanozyme when compared with the case of the Fe 3 O 4 nanozyme.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon has been observed for several different metal adatoms on Fe 3 O 4 (001) before and the foreign adatom can either substitute a 5-fold coordinated surface Fe oct or incorporate in the vacant octahedral site of the SCV reconstruction. [13][14][15]29 Schematic representations of the three possible sites of Rh 1 near the surface are shown in insets in Fig. 2a.…”
Section: Methodsmentioning
confidence: 99%